2012
DOI: 10.1007/s10336-012-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Kin structure and choice of brood care in a Common Eider (Somateria m. mollissima) population

Abstract: We investigated the presence of kin-biased cooperative breeding in the Common Eider (Somateria m. mollissima), a colonial seaduck commonly presumed to have a high rate of natal philopatry. Based on a 23-yearlong time series of individually marked mothers and daughters, we found that on average 18% of the study population consisted of first-order relatives: mothers, daughters, and female siblings. However, there were years with no or only a few first-order kin pairs present. This was due to the overall low duck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In this study, our objectives were to (a) genotype nest feathers and hatch membranes to identify instances of conspecific brood parasitism, (b) quantify the level of relatedness between host and parasitizers to estimate the inclusive fitness of parasitic eggs to the host female, and (c) understand the underlying mechanism (kin grouping or nest site fidelity) responsible for high levels of relatedness observed between host and parasitizer. Our overall estimate of brood parasitism (22.7% of eggs and 50.7% of nests) is comparable to other estimates for this species using microsatellite genotyping: higher than the rate of 17% of eggs estimated by Tiedemann et al () and lower than the rate of 34.2% of eggs estimated by Hario et al () (Table ). We also found our estimate of parasitism to be higher than other methods used such as protein banding and morphometrics, which is due to microsatellites having a higher probability of detecting cases of parasitism (Table ; Figure ).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, our objectives were to (a) genotype nest feathers and hatch membranes to identify instances of conspecific brood parasitism, (b) quantify the level of relatedness between host and parasitizers to estimate the inclusive fitness of parasitic eggs to the host female, and (c) understand the underlying mechanism (kin grouping or nest site fidelity) responsible for high levels of relatedness observed between host and parasitizer. Our overall estimate of brood parasitism (22.7% of eggs and 50.7% of nests) is comparable to other estimates for this species using microsatellite genotyping: higher than the rate of 17% of eggs estimated by Tiedemann et al () and lower than the rate of 34.2% of eggs estimated by Hario et al () (Table ). We also found our estimate of parasitism to be higher than other methods used such as protein banding and morphometrics, which is due to microsatellites having a higher probability of detecting cases of parasitism (Table ; Figure ).…”
Section: Discussionsupporting
confidence: 81%
“…This view is corroborated by the observations that breeding dispersal distances are very short (Ö st et al 2011) and that shifts between nesting islands are rare (Ekroos et al 2012b). In contrast, natal dispersal, which is unfortunately poorly documented in eiders due to practical constraints, may be much higher than previously realized (Hario et al 2012). This opens up the possibility that immigration and emigration during natal dispersal may profoundly affect local and regional population dynamics.…”
Section: Source-sink Dynamics and Management Challengesmentioning
confidence: 76%
“…In itself this idea is not new, as Ö st et al (2005) suggested that strict natal philopatry to nesting islands is not the rule in Tvärminne, based on the finding that genetic differentiation between islands is absent. Moreover, Hario et al (2012) reported a low frequency of first-order kin associations at Söderskär, and extensive movement between the natal and breeding sites of recruiting females born in the Söderskär colony. These strands of empirical evidence, suggesting that natal dispersal may be more extensive than currently recognized, are significantly strengthened by our analysis of stochastic growth rate.…”
Section: Differences Between Model-predicted and Observed Growth Ratesmentioning
confidence: 97%
“…There is evidence of kin synchrony in nesting snow geese Anser caerulescens (Findlay & Cooke, ). In eiders no strong effect was found of heritable similarity in breeding time between close relatives (Hario et al ., ).…”
Section: Causes Of Host–parasite Relatednessmentioning
confidence: 99%
“…The male follows his mate to her breeding area, often near her birth site (Anderson et al, 1992). Some neighbour females are therefore related, with potential consequences for social behaviour and inclusive fitness (Andersson &Åhlund, 2000;McKinnon, Gilchrist & Scribner, 2006;Roy Nielsen et al, 2006c;Waldeck et al, 2008;Jaatinen et al, 2009aJaatinen et al, , 2011bAnderholm et al, 2009b;Sonsthagen et al, 2010;Fishman et al, 2011;Hario, Koljonen & Rintala, 2012). Most ducks have dispersed nests, but common eiders (Somateria mollissima) and geese often breed in colonies, where high nest density facilitates CBP.…”
Section: Waterfowl Reproductionmentioning
confidence: 99%